PENGGUNAAN METODE PEMBELAJARAN FONIK DALAM MENINGKATKAN KEMAMPUAN BACA SISWA di TADIKA DIDIK BISTARI GEMILANG GERIK,PERAK MALAYSIA - Hanum, Aminah; Rahman, Abd (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Phonics is a method of learning to read and write which involves learning how to connect spoken letter sounds from the letters of the alphabet. This research was conducted for 21 days at Tadika Didik Bistari Gemilang Gerik, Perak Malaysia to see students' reading abilities. The methods in this research are observation, interviews and documentation. The data in this study were analyzed descriptively to describe the subject's reading development. The conclusion of this research is that the use of phonics learning methods is effective in improving students' reading skills at Tadika Didik Bistari Gemilang Gerik, Perak Malaysia. The results showed a significant increase in reading ability, more positive results than conventional methods, and increased student learning motivation.